IMPLEMENTASI FILTER AUGMENTED REALITY SEBAGAI STRATEGI BRAND MARKETING UNTUK MENINGKATKAN PENJUALAN - Arista Febrian Nugraha; Syaipul Ramdhan; Nyi Dewi Puspitasari (Jurnal Teknoinfo, 2023)
This study discusses the application of Augmented Reality (AR) filters in brand marketing strategies to increase sales. AR filters enable companies to create creative content that captures consumer attention, increases engagement and strengthens brand awareness. AR filters provide consumers with a personalized experience, enabling interaction with brands through unique visual displays. In a marketing context, AR filters can increase social engagement and extend brand reach through sharing user experiences on social media. AR filter usage data can provide valuable analytical insights for optimizing marketing campaigns. This study analyzes examples of using AR filters, challenges, and provides practical recommendations for companies wishing to adopt this strategy. Metric data shows 2.3k times opened, 866 times image captured, 126 times saved, 218 times shared, 1.1k used, 567 impressions. Usage results showed a significant increase in sales of Benfarm products from 61 pcs in April to 156 in May, sales up 200%.